MENINGKATKAN MINAT DAN HASIL BELAJAR VOKAL DENGAN MENERAPKAN METODE SOLFEGIO - Asmoro, Ari (Jurnal Penelitian Pendidikan, 2014)
In learning process, specific approach is needed in order to achieve the expected outcome. The approach is usually in a form of method related to the material being taught. Vocal learning in the classroom often often makes students less interested, this is proven by the test result which shows that 30% of the students are below the minimum passing score criteria. The implementation of solfegio method aims to improve the students’ interest in learning vocal so that the students will achieve maximum learning outcome above the minimum passing score criteria. This classroom research aims to improve students’ interest in learning vocal and improving their learning outcome by using solfegio method. The object of this research were the students of SMP 2 Pemalang grade VIII E. The method used in the research is classroom action research, it is a research aiming to solve classroom problems. The research was conducted in two cycles, each cycle consists of: planning, observation, action, and reflection. The data were collected through: documentation, observation, questionnaire, and test. The data analysis technique used in this research are descriptive quantitative and descriptive qualitative. From the vocal learning prosess in VIII E Class at SMP N 2 Pemalang, which has been carried out through the analysis of action research with two cycles, it can be concluded that vocal learning by using solfegio method has given positive impacts in improving students learning outcome indicated by the improvement of their minimum passing score criteria. Only 41% students passed the minimum criteria in cycle 1, and then it reached 89% in cycle 2. In addition, the application of the solfegio method have a positive effect, which can increase student interest shown by the average of the students’ answers result to the questionnaire which states that students are interested in vocal training with solfegio method. So the conclusion from this study is that the solfegio method gives positive effect on vocal learning to the students at SMP 2 Pemalang.